Kejadian 2:24 dan Arsitektur Perjanjian Pernikahan Kristen: Analisis Integratif atas Monogami, Gender, dan Kesatuan - Ragil Kristiawan; Pujiati Pujiati; Kim Kiedong (Sekolah Tinggi Teologi Parakletos Tomohon, 2026)
Abstract: This study conducts an integrative exegetical analysis of Genesis 2:24 as the theological foundation of Christian marriage. It reveals four interrelated principles within the divine design of marriage: monogamy, heterosexuality, independence (leaving), and physical unity (one flesh). These four principles form a coherent theological architecture in which each aspect mutually reinforces and defines the others. Monogamy reflects God's faithfulness, heterosexuality is based on gender complementarity in creation, independence is a prerequisite for forming a new family unit, and the